Hydrophobically Modified Polyacrylamide Synthesis and Application in Water Treatment: A Review - Liao, Yi; Zheng, Huaili; Dai, Li; Li, Fengting; Zhu, Guocheng; Guan, Qingqing; Sun, Yongjun; Tang, Xiaomin (Asian Journal of Chemistry, 2014)
This review examines recent advances in the synthesis of hydrophobically modified polyacrylamide. The synthetic method includes direct copolymerization and post polymerization, and direct copolymerization mainly includes heterogeneous copolymerization, homogeneous copolymerization, micellar polymerization, microemulsion polymerization, soap-free polymerization and polymerization in supercritical CO2. In addition, the application of hydrophobically modified polyacrylamide in water treatment is examined. Based on these reviews, future research prospect relating to its synthesis and application in water treatment were proposed.